P196 Cryo-recanalisation via day-case flexible bronchoscopy for central airway obstruction. (16th November 2010) - Ng, B; Oltmanns, U; Hardy, C; Yip, C; Slade, M
Abstract : Introduction and Objectives: The use of a flexible cryoprobe to effect bronchial recanalisation inpatients with central airway obstruction (CAO) has previously been described, in patients under general anaesthesia undergoing rigid bronchoscopy (C Schumann et al. J Thorac Cardiovasc Surg 2010;139 :997–1000). Few data on flexible bronchoscopic cryorecanalization have been published. Methods: All flexible interventional bronchoscopic procedures were recorded prospectively in adatabase, and data extracted on all procedures in which cryo-recanalisation (Erbokryo, ERBE UK Ltd) was attempted. Data collected included demographics, diagnosis, indication for procedure and site of tracheobronchial abnormality, techniques used, complications and the following data pre- and post-procedure: performance status, FEV1, patient location. The procedure duration, defined as the time in minutes between initial bronchoscope insertion and final bronchoscope withdrawal, was recorded in 23 cases. Bronchoscopies were performed in Oxford and Papworth by, or under the direct supervision of, a single operator (MS). Results: Between May 2006 and July 2010, 54 procedures were performed in 46 patients (13 female, 33male). The median age was 69 (range 24–94). The underlying diagnosis was lung cancer in 39 procedures, endobronchial metastases in 13 and benign disease in 2 (post tracheostomy granulation tissue in 1, thrombus in 1). All patients had CAO affecting a lobar or more proximal bronchus. There was a mean improvement in FEV1 of 0.28L (mean (SD) FEV1 pre-procedure 1.56L (0.71L), mean (SD) FEV1 post procedure 1.84L (0.80), p=0.001, paired t-test). Median performance status was 1 both before and after the procedure. In 49/54 procedures (91%) the patients were treated as day-cases, and 5/54 (9%) as inpatients. Bleeding complications occurred in two patients. In both cases bleeding of >50 mls occurred, which was controlled using epinephrine via the bronchoscope. The median procedure duration was 20 (range 7–58) min. Conclusions: Day-case cryorecanalization via flexible bronchoscopy appears to offer effective improvement in lung function in patients with CAO owing to endobronchial lesions. Procedure duration is short, and complication rates appear acceptable. We believe that cryo-recanalisation using flexible cryoprobes deserves more widespread use in centres specialising in interventional bronchoscopy.